2006
DOI: 10.1177/0272431605285720
|View full text |Cite
|
Sign up to set email alerts
|

Family Processes Mediating the Relationship of Neighborhood Disadvantage to Early Adolescent Internalizing Problems

Abstract: The objective of the current study was to examine the relationships among neighborhood disadvantage, perceived neighborhood quality, family processes, and child internalizing problems within the framework of social disorganization theory. The sample consisted of 189 low-income, European American and Mexican American children and their mothers. The data analyses partially supported our hypotheses that mothers' perceptions of neighborhoods mediated the relation of neighborhood disadvantage to family processes, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 47 publications
4
79
2
1
Order By: Relevance
“…In another study on victimization and bullying among 73 children among 46 classrooms and 18 schools (Bonnet, Goossens, & Schuengel, 2011), the authors reasoned that as the average number of children in a classroom was 1.6, the design effect must be smaller than 2, and they chose the single-level regression analysis rather than the multilevel model. From our literature review in PsycINFO and ERIC, we found many similar studies in the field of education using this rule as a justification for not using multilevel models for multilevel/clustered data (e.g., Bouman et al, 2012;De Los Reyes et al, 2011;Deng et al, 2006;Hong & You, 2012;Linnenbrink-Garcia, Rogat, & Koskey, 2011;Ly, Zhou, Chu, & Chen, 2012;Von Grünigen, Kochenderfer-Ladd, Perren, & Alsaker, 2012;Wong et al, 2006). This rule was also commonly used in other research areas such as psychology (e.g., Corte & Zucker, 2008;Wagner, Christ, Pettigrew, Stellmacher, & Wolf, 2006), business (Qureshi & Fang, 2011), and medical science (Fuentes, Hart-Johnson, & Green, 2007).…”
mentioning
confidence: 89%
“…In another study on victimization and bullying among 73 children among 46 classrooms and 18 schools (Bonnet, Goossens, & Schuengel, 2011), the authors reasoned that as the average number of children in a classroom was 1.6, the design effect must be smaller than 2, and they chose the single-level regression analysis rather than the multilevel model. From our literature review in PsycINFO and ERIC, we found many similar studies in the field of education using this rule as a justification for not using multilevel models for multilevel/clustered data (e.g., Bouman et al, 2012;De Los Reyes et al, 2011;Deng et al, 2006;Hong & You, 2012;Linnenbrink-Garcia, Rogat, & Koskey, 2011;Ly, Zhou, Chu, & Chen, 2012;Von Grünigen, Kochenderfer-Ladd, Perren, & Alsaker, 2012;Wong et al, 2006). This rule was also commonly used in other research areas such as psychology (e.g., Corte & Zucker, 2008;Wagner, Christ, Pettigrew, Stellmacher, & Wolf, 2006), business (Qureshi & Fang, 2011), and medical science (Fuentes, Hart-Johnson, & Green, 2007).…”
mentioning
confidence: 89%
“…A study of Latino youth and families, for example, found that neighborhood crime, combined with maternal distress and perceived financial strain, was associated with disrupted family routines (Prelow, Loukas, & Jordan-Green, 2007). Lower levels of neighborhood cohesion, or willingness to intervene on behalf of fellow residents, has also been linked to lower levels of family cohesion (Deng et al, 2006). Importantly, urban neighborhoods have been found to possess higher concentrations of many of the community characteristics associated to date with compromised family relationships (e.g., crime, violence; Department of Justice, 2004).…”
Section: Influences On the Coparenting Relationshipmentioning
confidence: 99%
“…Lack of neighborhood resources and social isolation deprives parents of the support of neighbors and community resources that are often useful in parenting efforts and reducing stress (Beeber et al 2008; Deng et al 2006). …”
Section: Introductionmentioning
confidence: 99%